Lumostatic operation controlled by the optimum light intensity per dry weight for the effective production of Chlorella zofingiensis in the high cell density continuous culture - Imaizumi, Yuki; Nagao, Norio; Md Yusoff, Fatimah; Kurosawa, Norio; Kawasaki, Nobuyuki; Toda, Tatsuki (Elsevier, 2016)
To maximize the production rate of Chlorella zofingiensis, a lumostatic continuous culture was operated under light intensities of 250–1510 μE m− 2 s− 1. The cell density and volumetric biomass production rate were increased without photo inhibition and reached 13.5 g-dry weight (dw) L− 1 on day 21.5 and 2.41 g-dw L− 1 day− 1 on day 10.5, respectively. These maximum values were higher than any previous photoautotrophic culture study with C. zofingiensis. The specific growth rate was maintained at a high level > 0.5 day− 1 until the light intensity per dry weight decreased below 28 μE g-dw− 1 s− 1, which coincided with the value estimated in our previous study, verifying the reliability of this estimated value. There was a strong relationship between the photosynthetic efficiency and light intensity per dry weight for C. zofingiensis. This relationship may be useful for evaluating species-specific productivity to select productive species.